The Role of Cathepsin B in the Degradation of Aβ and in the Production of Aβ Peptides Starting With Ala2 in Cultured Astrocytes - Oberstein, Timo Jan; Utz, Janine; Spitzer, Philipp; Klafki, Hans Wolfgang; Wiltfang, Jens; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel (Frontiers in Molecular Neuroscience, 2021)
Astrocytes may not only be involved in the clearance of Amyloid beta peptides (Aβ) in Alzheimer´s disease (AD), but appear to produce N-terminally truncated Aβ (Aβn-x) independently of BACE1, which generates the N-Terminus of Aβ starting with Asp1 (Aβ1-x). A candidate protease for the generation of Aβn-x is cathepsin B (CatB). Especially since CatB has also been reported to degrade Aβ, which could explain the opposite roles of astrocytes in AD. In this study, we investigated the influence of CatB inhibitors and the deletion of the gene encoding CatB (CTSB) using CRISPR/Cas9 technology on Aβ2-x and Aβ1-x levels in cell culture supernatants by one- and two-dimensional Urea-SDS-PAGE followed by immunoblot. While the cell-permeant inhibitors E64d and CA-074 Me did not significantly affect the Aβ1-x levels in supernatants of cultured chicken and human astrocytes, they did reduce the Aβ2-x levels. In the glioma-derived cell line H4, the Aβ2-x levels were likewise decreased in supernatants by treatment with the more specific, but cell-impermeant CatB-inhibitor CA-074, by CA-074 Me treatment, and by CTSB gene deletion. Additionally, a more than twofold increase in secreted Aβ1-x was observed under the latter two conditions. The CA-074 Me-mediated increase of Aβ1-x, but not the decrease of Aβ2-x, was influenced by concomitant treatment with the vacuolar H+-ATPase inhibitor Bafilomycin A1. This indicated, that non-lysosomal CatB mediated the production of Aβ2-x in astrocytes, while the degradation of Aβ1-x seemed to be dependent on lysosomal CatB in H4 cells, but not in primary astrocytes. These findings highlight the importance of considering organelle targeting in drug development to promote Aβ degradation.